2014
DOI: 10.9756/bijiems.4741
|View full text |Cite
|
Sign up to set email alerts
|

Architecture and Adoption Model for Cloud in Higher Education: Indian Perspective

Abstract: Cloud implementation is seen as a possible rescue measure to the financial crisis faced by higher education (HE) institutes due to the shrinking IT budgets and escalating IT needs.In this paper, architecture for implementing cloud in the HE institute involving various Deployment Models and Service Models is proposed. A five step framework based on Roger's Innovation-Diffusion model has been suggested for adopting cloud in HE institutes. For smoothing the migration from traditional system to cloud based system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Khurana et al, (2012), Sambasivan & Fei, (2008), Noorul Haq & Kannan, (2006), Pardeshi, (2014 Time (TM) Rogers (2003), Derwisch et al (2015), Sarpong et al (2016), Gopalakrishnan and Damanpour (1994), Tsai and Hung (2014) Acknowledgement The authors extend thanks to Dr. Sanjay Kumar, Dr. Sunil Luthra and anonymous experts for sparing their precious time and giving useful comments and suggestions that helped in improving the quality of research. The authors would also like to acknowledge Jamia Millia Islamia and MoMA, Govt.…”
Section: Communication Network (Cn)mentioning
confidence: 99%
“…Khurana et al, (2012), Sambasivan & Fei, (2008), Noorul Haq & Kannan, (2006), Pardeshi, (2014 Time (TM) Rogers (2003), Derwisch et al (2015), Sarpong et al (2016), Gopalakrishnan and Damanpour (1994), Tsai and Hung (2014) Acknowledgement The authors extend thanks to Dr. Sanjay Kumar, Dr. Sunil Luthra and anonymous experts for sparing their precious time and giving useful comments and suggestions that helped in improving the quality of research. The authors would also like to acknowledge Jamia Millia Islamia and MoMA, Govt.…”
Section: Communication Network (Cn)mentioning
confidence: 99%
“…B. Ali, 2019; K. E. Ali et al, 2018; Alonso-Monsalve et al, 2018; Juma & Tjahyanto, 2019; Pardeshi, 2014; Rao et al, 2013; Sabi et al, 2016). The NIST proposes four different cloud organization models and cloud management models in cloud computing design (Liu et al, 2012).…”
Section: An Abstract Hybrid Cloud Framework For Universitiesmentioning
confidence: 99%
“…According to Takai (2012), the transition to the cloud consists of the following steps: the promotion of cloud computing, data center consolidation, establishment of the enterprise cloud infrastructure, and submission of cloud services (Takai, 2012). For a smooth transition from traditional system to cloud-based system, Pradesh (Pardeshi, 2014) suggested a five-step framework: confirmation, implementation, decision, knowledge and, persuasion. Attaran et al (2017) identified the three phases of the cloud service adoption strategy for successful implementation of cloud in two universities, Bryant (BU) and Roger Williams (RWU).…”
Section: Steps For a Successful Transition To Cloudmentioning
confidence: 99%
See 1 more Smart Citation
“…Pardeshi (2014) proposed a cloud-based IT architecture, consisting of various deployment and service models, the IaaS as a foundation layer, with PaaS build upon IaaS, and followed by SaaS build upon PaaS for implementing cloud in the HE institute. A five-step framework based on Roger's Innovation-Diffusion model has been suggested for adopting cloud in HE institutes.…”
mentioning
confidence: 99%